Low-resolution pressure reactivity index and its derived optimal cerebral perfusion pressure in adult traumatic brain injury: a CENTER-TBI study - Riemann, Lennart; Beqiri, Erta; Smielewski, Peter; Czosnyka, Marek; Stocchetti, Nino; Sakowitz, Oliver; Zweckberger, Klaus; Unterberg, Andreas; Younsi, Alexander (Critical care, 2020)
Background: After traumatic brain injury (TBI), brain tissue can be further damaged when cerebral autoregulation is impaired. Managing cerebral perfusion pressure (CPP) according to computed "optimal CPP" values based on cerebrovascular reactivity indices might contribute to preventing such secondary injuries. In this study, we examined the discriminative value of a low-resolution long pressure reactivity index (LPRx) and its derived "optimal CPP" in comparison to the well-established high-resolution pressure reactivity index (PRx). Methods: Using the Collaborative European NeuroTrauma Effectiveness Research in Traumatic Brain Injury (CENTER-TBI) study dataset, the association of LPRx (correlation between 1-min averages of intracranial pressure and arterial blood pressure over a moving time frame of 20min) and PRx (correlation between 10-s averages of intracranial pressure and arterial blood pressure over a moving time frame of 5min) to outcome was assessed and compared using univariate and multivariate regression analysis. "Optimal CPP" values were calculated using a multi-window algorithm that was based on either LPRx or PRx, and their discriminative ability was compared. Results: LPRx and PRx were both significant predictors of mortality in univariate and multivariate regression analysis, but PRx displayed a higher discriminative ability. Similarly, deviations of actual CPP from "optimal CPP" values calculated from each index were significantly associated with outcome in univariate and multivariate analysis. "Optimal CPP" based on PRx, however, trended towards more precise predictions. Conclusions: LPRx and its derived "optimal CPP" which are based on low-resolution data were significantly associated with outcome after TBI. However, they did not reach the discriminative ability of the high-resolution PRx and its derived "optimal CPP." Nevertheless, LPRx might still be an interesting tool to assess cerebrovascular reactivity in centers without high-resolution signal monitoring.Trial registrationClinicalTrials.gov Identifier: NCT02210221. First submitted July 29, 2014. First posted August 6, 2014.